2018
DOI: 10.11137/2018_3_207_215
|View full text |Cite
|
Sign up to set email alerts
|

Drone in the Environmental Audit: Potentialities and Applications

Abstract: As Aeronaves Remotamente Pilotadas (RPA), conhecidas popularmente como Drones, são ferramentas capazes de gerar produtos de sensoriamento remoto de elevada acurácia, com grande perspectiva de potencial para utilização no processo de Auditoria Ambiental, executando tarefas antes exclusivas de aeronaves tripuladas. Entretanto, por se tratar de uma tecnologia relativamente recente, justifica-se a necessidade de ponderar a aplicabilidade do seu uso em estudos ambientais, sendo o objetivo deste artigo, avaliar as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…e results showed that the timely disclosure of environmental information was affected by the environmental audit committee, CSR (Corporate Social Responsibility) committee, the auditors, earnings management behavior, firm size, and the industry, while no evidence has been found that there is a statistically significant relationship between CSR committee and the voluntary disclosure of environmental information [6]. Silva et al (2018) aimed to assess the potential and application of UAVs (Unmanned Aerial Vehicles) in environmental audit and proposed a method for data acquisition and identification of environmental impacts [7]. In conclusion, much literature has attached the importance to environmental audit especially in the era of the COVID-19 (SARS-CoV-2) virus, but unfortunately, so far, few studies have directly explored the environmental protection-oriented ecoenvironmental performance audit in the Yangtze River Economic Belt.…”
Section: Research Methods and Related Literature Onmentioning
confidence: 98%
“…e results showed that the timely disclosure of environmental information was affected by the environmental audit committee, CSR (Corporate Social Responsibility) committee, the auditors, earnings management behavior, firm size, and the industry, while no evidence has been found that there is a statistically significant relationship between CSR committee and the voluntary disclosure of environmental information [6]. Silva et al (2018) aimed to assess the potential and application of UAVs (Unmanned Aerial Vehicles) in environmental audit and proposed a method for data acquisition and identification of environmental impacts [7]. In conclusion, much literature has attached the importance to environmental audit especially in the era of the COVID-19 (SARS-CoV-2) virus, but unfortunately, so far, few studies have directly explored the environmental protection-oriented ecoenvironmental performance audit in the Yangtze River Economic Belt.…”
Section: Research Methods and Related Literature Onmentioning
confidence: 98%